Strategi Implementasi Inquiry Learning Model Untuk Meningkatkan Critical Thinking Skills Siswa Berbantuan ChatGPT - Rismayanti, Epa; Purmadi, Ary (Penerbit Widina, Widina Media Utama, 2025)
The use of ChatGPT in learning has been carried out massively, especially by learners. However, often the use of ChatGPT is not carried out with the integration of morals, ethics, and critical thinking activities. A certain approach or strategy is needed in integrating ChatGPT into learning activities in order to help students develop critical and analytical thinking to solve a problem. Departing from these problems, the purpose of this study is to identify and develop a strategy for implementing an inquiry learning model to improve critical thinking skills in students by utilizing ChatGPT media wisely. This study uses the SLR method with a systematic and in-depth analysis of previous research results. This study produces results that educators need to condition ChatGPT as a supporting medium for learning with a dominance of providing various learning resources in various formats to support information collection and review activities in problem-solving efforts. In addition, the practical implications of the findings of this study are the need for an active role for educators to help and facilitate students in developing critical reasoning in responding to information which of course integrates morals and ethics in using it.ABSTRAKPemanfaatan ChatGPT dalam pembelajaran telah masif dilakukan terutama oleh kalangan pembelajar. Namun sering kali pemanfaatan ChatGPT ini tidak diiringi dengan pengintegrasian moral, etika serta aktivitas berpikir kritis. Diperlukan pendekatan atau strategi tertentu dalam mengintegrasikan ChatGPT pada aktivitas pembelajaran agar dapat membantu siswa untuk menumbuhkan pemikiran kritis dan analitis untuk memecahkan suatu persoalan. Berangkat dari persoalan tersebut, tujuan dilaksanakannya penelitian ini yaitu untuk mengidentifikasi dan merumuskan strategi implementasi inquiry learning model untuk meningkatkan critical thinking skills pada siswa dengan memanfaatkan media ChatGPT secara bijak. Penelitian ini menggunakan metode SLR dengan analisa sistematis dan mendalam hasil penelitian terdahulu. Penelitian ini membuahkan hasil bahwa pendidik perlu mengondisikan ChatGPT sebagai media pendukung pembelajaran dengan dominasi penyediaan berbagai sumber belajar dalam berbagai format untuk mendukung aktivitas pengumpulan dan pengkajian informasi dalam upaya pemecahan masalah. Selain itu, implikasi praktis dari temuan penelitian ini yaitu perlunya peran pendidik secara aktif untuk membantu dan menfasilitasi siswa dalam mengembangkan nalar kritis dalam menyikapi suatu informasi yang tentunya mengintegrasikan moral dan etika dalam menggunakannya